Design and Implementation of Comparative Accelerated Life Test for Solder Joints Based on Failure Mechanism - Fan YANG (机车电传动)
In order to solve the shortcomings of traditional accelerated life test, such as long test time and large sample size, it is necessary to design comparative accelerated life test. Firstly, through the analysis of the failure mechanism of through-hole solder joints, the failure sensitive stress was defined; Secondly, based on the previous statistical information and the failure sensitive stress, the comparative accelerated life test scheme was designed; Finally, the comparative accelerated life test was carried out for the reference plug-in through-hole solder joints, and the life level of the through-hole solder joints to be evaluated was verified. The results showed that compared with the traditional accelerated life test, the comparative accelerated life test required shortened test time and fewer samples. Referring to the life benchmark of reference plug-in through-hole solder joints, it was verified that the life of the evaluated plug-in through-hole solder joints was less than 10 years, and the process improvement was needed.